User Acceptance for Multitask IoT Monitoring and Controlling System for Salt Ponds - Yudantoro, Tri Raharjo; Hamida, Busra Nur; Febriyanti, Eka; Wiktasari, Wiktasari; Pernanda, Suko Tyas; Prabuwono, Anton Satria (Indonesian Journal of Information Systems, 2023)
The process of making salt is still done manually by filling water into reservoirs and plots which require salt farmers to visit their farms periodically. This is mainly because the speed of the salt crystalization process is always inconsistent due to salt concentration in seawater and the weather. This study aims to build a new prototype of a water level monitoring system in reservoirs and plots in salt ponds then measure the water's salinity value, which will be reported to the farmers. The method used in this research is prototyping, which includes system requirement analysis, rapid design, prototype building, system evaluation, and system  improvement. The system was tested using the black box method, namely testing all system functionality and determining user satisfaction with questionnaires. The functionality test results, including monitoring the water level and the pump control, show that the prototype functions correctly. The designed system can send information in the form of water level values in reservoirs, water levels in plots, and salinity values with linear sensor accuracy with measurement results with conventional measuring instruments with standard error values of 0.485, 0.44, and 0.72, respectively. Applying this system will ease farmers’ monitoring of water levels and controlling irrigation in reservoirs and plots.